2017
DOI: 10.1088/1674-1056/26/6/067401
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, and vibrational properties of phase H: A first-principles simulation

Abstract: Phase H (MgSiO 4 H 2 ), one of the dense hydrous magnesium silicates (DHMSs), is supposed to be vital to transporting water into the lower mantle. Here the crystal structure, elasticity and Raman vibrational properties of the two possible structures of phase H with Pm and P2/m symmetry under high pressures are evaluated by first-principles simulations. The cell parameters, elastic and Raman vibrational properties of the Pm symmetry become the same as the P2/m symmetry at ∼ 30 GPa. The symmetrization of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The Fe-bearing phase H structures were constructed by Tschermak substitution of Mg 2+ by Fe 2+ in the Mg endmember phase H. The three Fe-bearing phase H (FeSiO 4 H 2 (Pure-Fe, 100at%), M g0.75 Fe 0.25 SiO 4 H 2 (High-Fe, 25at%), and Mg 0.875 Fe 0.125 SiO 4 H 2 (Low-Fe, 12.5at%)) were built and simulated in this work. The Mg end-member phase H (MgSiO 4 H 2 ) (Pure-Mg) and Al end-member phase H (Al 2 O 4 H 2 ) (Pure-A) were cited from the previous works [Liu et al, 2017[Liu et al, , 2018 for understanding the effect of Fe on the crystal structure and elastic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe-bearing phase H structures were constructed by Tschermak substitution of Mg 2+ by Fe 2+ in the Mg endmember phase H. The three Fe-bearing phase H (FeSiO 4 H 2 (Pure-Fe, 100at%), M g0.75 Fe 0.25 SiO 4 H 2 (High-Fe, 25at%), and Mg 0.875 Fe 0.125 SiO 4 H 2 (Low-Fe, 12.5at%)) were built and simulated in this work. The Mg end-member phase H (MgSiO 4 H 2 ) (Pure-Mg) and Al end-member phase H (Al 2 O 4 H 2 ) (Pure-A) were cited from the previous works [Liu et al, 2017[Liu et al, , 2018 for understanding the effect of Fe on the crystal structure and elastic properties.…”
Section: Resultsmentioning
confidence: 99%
“…For ferrous iron (Fe 2+ ) in this work, we consider the high spin ferromagnetic state (spin momentum S=4/2) during the calculation [Zhang and Oganov, 2006;Li et al, 2005;Hsu et al, 2011Hsu et al, , 2012. The benchmark calculations can be seen in the previous works [Liu et al, 2017[Liu et al, , 2018.…”
Section: Simulations Detailsmentioning
confidence: 99%
“…An experimental study on δ-AlOOH, the topologically equivalent structure to phase H, found that the O-H stretching modes exist between 2100 and 2700 cm -1 at 0 GPa (Ohtani et al 2017) on phase H using the CASTEP software package (Segall et al 2002) produce very similar vibrational frequencies to those of this study (Supplementary Figure 2). The relative intensities of the O-H stretching modes are much stronger in the study of Lv et al (2017), possibly due to the different configuration and different computational details, such as the use of norm-conserving pseudopotentials instead of the PAW potentials for structural relaxations and the implementation of CASTEP instead of ABINIT for calculating the Raman phases: ~2000 cm -1 for ice X extrapolated to 25 GPa (Caracas 2008), ~2700 cm -1 for ice VII at GPa (Hernandez and Caracas 2018), and 2500-3000 cm -1 for dimer acids at ambient pressure (Chen et al 2017) where the O-H environments are highly constrained.…”
Section: Raman Vibrational Modesmentioning
confidence: 98%
“…Both Mg-Egg and P4 3 2 1 2 phases show concave-down parabolic curves in F-f space that call for the use of the fourth-order Birch-Murnaghan equations of state (Fig.4inset). The situation for phase H is complex; the Pm structure of phase H undergoes a second-order phase transition to the P2/m structure at about 30 GPa due to H-O bond symmetrization(Tsuchiya and Mookherjee 2015;Lv et al 2017). The phase transition is subtle in pressure-volume space but manifests as a clear break in slope at f = 0.05 in the F-f plot.The linearity of the low-pressure region warrants the use of a third-order Birch-Murnaghan equation of state between 0 and 25 GPa, while the concave-down behavior of the high-pressure region warrants the use of a fourth-order Birch-Murnaghan equation of state between 35 and 140…”
mentioning
confidence: 99%
“…Based on the principle of quantum mechanics and density functional theory, it uses the Hohenberg-Kohn theorem (Hohenberg and Kohn, 1964) to determine the system's energy and calculate the properties of molecules and condensed matter. First-principles calculations have been successfully applied to geosciences for understanding mineral properties such as structural, elastic, and electrical properties under high pressure and temperature (Gillan et al, 2006;Jahn and Kowalski, 2014;Karki, 2014;Liu et al, 2015;Zhang et al, 2015a;Zhang et al, 2015b;Zhao et al, 2015;Wu and Wentzcovitch, 2016;Lv et al, 2017;Umemoto et al, 2017). Therefore, we investigate the crystal structural and elastic properties of CaO 3 under high pressure using first-principles calculations to discover the far-reaching significance and influence of CaO 3 in the mantle transition zone and lower mantle.…”
Section: Introductionmentioning
confidence: 99%